2022
DOI: 10.1021/acssuschemeng.1c07869
|View full text |Cite
|
Sign up to set email alerts
|

Green Mechanochemical Strategy for the Construction of a New Bio-based Nylon 524T Ternary Salt

Abstract: Green chemistry calls for reducing the use of environmentally harmful materials and petroleum resources. Bio-based nylon materials can help address this problem. In this study, a new bio-based nylon 524T ternary salt was discovered and constructed by a green mechanochemical method based on the pharmaceutical cocrystal screening and synthesis strategy. The effects of adding solvents and grinding times on the formation of a ternary salt were systematically studied, and the formation of a nylon 524T ternary salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…High-quality monomers are essential to the synthesis of excellent performance polymers, and crystallization technology is a convenient method for the efficient preparation and purification of monomers. 24–26 During our research, we found that PDA-OPA exists in four crystal forms in crystallization experiments, one MeOH solvate and three hydrates (named monohydrate, dihydrate, and trihydrate). Meanwhile, we also accidentally obtained two anhydrous forms with non-equimolar ratios, named anhydrate-I and anhydrate-II, and another anhydrous form III, but only single crystals of I and II were obtained.…”
Section: Introductionmentioning
confidence: 82%
“…High-quality monomers are essential to the synthesis of excellent performance polymers, and crystallization technology is a convenient method for the efficient preparation and purification of monomers. 24–26 During our research, we found that PDA-OPA exists in four crystal forms in crystallization experiments, one MeOH solvate and three hydrates (named monohydrate, dihydrate, and trihydrate). Meanwhile, we also accidentally obtained two anhydrous forms with non-equimolar ratios, named anhydrate-I and anhydrate-II, and another anhydrous form III, but only single crystals of I and II were obtained.…”
Section: Introductionmentioning
confidence: 82%
“…-the effects of adding solvents and grinding times on the formation of a ternary salt were systematically studied, and the formation of a nylon 524T ternary salt under solvent-assisted grinding was found to follow a mechanically driven dissolution-recrystallization mechanism [25];…”
Section: Introductionmentioning
confidence: 99%
“…In all, the extensive use of organic solvents in drug production will eventually translate into a huge environmental threat and considerable costs of waste treatment . Therefore, the development of sustainable chemical techniques has become a major trend. , As the principles of Green Chemistry advocate, the search for clean and cheap product processing that is safer and more efficient is an urgent challenge for the pharmaceutical industry. …”
mentioning
confidence: 99%